The development of real-time substructure testing - Blakeborough, A; Williams, M; Darby, A; Williams, D (2001)
Full-scale dynamic testing of civil engineering structures is extremely costly and difficult to perform. Most test methods therefore involve either a reduction in the physical scale or an extension of the time-scale. Both of these approaches can cause significant difficulties in extrapolating to the full-scale dynamic behaviour, particularly when the structure responds nonlinearly or includes highly rate-dependent components such as dampers. Real-time substructure testing is a relatively new method which seeks to avoid these problems by performing tests on key elements of the structure at full or large scale, with the physical test coupled in real time to a numerical model of the surrounding structure. The method requires a high performance of both the physical test equipment and the numerical algorithms. This paper first reviews the development of structural test methods and the emergence of real-time substructure testing. This is followed by a brief description of the equipment that is needed to implement a substructure test. Several novel developments in the numerical algorithms used in real-time substructure testing are presented, including a new, fast algorithm which allows nonlinear response of the surrounding structure to be computed in real time. Results are presented from a variety of tests which demonstrate the performance of the system at small and large scale, with either linear or nonlinear test specimens, and with varying numbers of degrees of freedom passed between the physical and numerical substructures. Finally, the usefulness and possible applications of the test method are discussed.